Expression Patterns and Functional Analysis of 11 E3 Ubiquitin Ligase Genes in Rice - Zhang, Huijuan; Zheng, Dewei; Song, Fengming; Jiang, Ming (Frontiers in Plant Science, 2022)
E3 ubiquitin ligases are involved in many processes, regulating the response to biotic and abiotic stresses. In this study, 11 E3 ubiquitin ligase genes were selected, and their functions were analyzed in rice. These 11 E3 ubiquitin ligase genes showed different patterns of expression under different treatments. The BMV:OsPUB39-infiltrated seedlings showed decreased resistance to Magnaporthe grisea (M. grisea) when compared with BMV:00-infiltrated seedlings, whereas the BMV:OsPUB34- and BMV:OsPUB33-infiltrated seedlings showed increased resistance. The involvement of these genes in the resistance against M. grisea may be attributed to the regulation of the accumulation of reactive oxygen species (ROS) and expression levels of defense-related genes. Seedlings infiltrated by BMV:OsATL69 showed decreased tolerance to drought stress, whereas BMV:OsPUB33-infiltraed seedlings showed increased tolerance, possibly through the regulation of proline content, sugar content, and expression of drought-responsive genes. BMV:OsATL32-infiltrated seedlings showed decreased tolerance to cold stress by regulating malondialdehyde (MDA) content and the expression of cold-responsive genes.